Compartment syndrome of the forearm following moderately displaced fracture of the radial head in a 10-year-old child - Jan, Wazir Fahad; Jahan, Alamgir; Yahya Dar, Mohd; Mushtaq Khan, Umar (International Journal of Research in Medical Sciences, 2017)
Compartment syndrome of the forearm is a rare complication of radial head fractures. We report the unsual case of a 10-year-old child who developed acute volar compartment syndrome of the forearm following a moderately displaced fracture of the radial head. The patient underwent volar fasciotomy of the forearm and open reduction of the radial head fracture with Krishner wire. Due to timely intervention the patient had a good postoperative outcome and is expected to have a good functional recovery.